Two-tier asymmetric information as a motive for trade, trade policies, and inefficient trade agreements - Bouët, Antoine; Laborde Debucquet, David; Martimort, David (International Food Policy Research Institute, 2014)
This theoretical paper intends to provide an explanation of the implementation of behind-the-border policies, border policies, and of the inefficiency of trade negotiations. We consider a general equilibrium model of international trade with two identical countries, two commodities, a terms-of-trade externality, and a double-tier informational problem. First, domestic producers have private information on their technology. This first layer of asymmetric information affects the design of behind-the-border policies. To reduce the information rent of those producers and ease incentive compatibility constraints, behind-the-border policies must contract domestic supply. Autarky prices are thus modified so that international trade appears. The informationally sensitive sector becomes an import sector and the more so, the greater the political influence of high-cost producers.